Custos energéticos do agroecossistema pinhão-manso e milho: comparativo entre o sistema de condução sequeiro e o irrigado - Frigo, Michelle Sato; Frigo, Elisandro; Bueno, Osmar de Carvalho [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP]; Klar, Antonio Evaldo [UNESP] (My University, 2011)
The knowledge production and energy expenditure in agriculture is crucial due to strategic importance which occupies as a producer of energy inputs to other economic sectors, such as biodiesel produced from oilseed crops, so this study was attempt to determine the energy cost of partial deployment and conduct of corn intercropping agroecosystem with physic nut, under the steering and without irrigation, in an experiment conducted in accordance with the productive system of family farming in the west of Paraná State. Such a study is justified due to the scarcity of energy data of the culture of physic nut under brazilian conditions, as well as in intercropping system under technological conditions of the family farm west of Paraná, and especially environmental issues involved in this study as the rational use of energy sources nonrenewable. The experiment was conducted in accordance with the techniques employed by family farmers in western Parana, from February 2008 to May 2008 for corn and from February 2008 to November 2009 for the cultivation of physic nut in the Experimental Center of Agricultural Engineering (NEEA), belonging to the State University of Western Paraná (UNIOESTE), campus of Cascavel/PR, in the area of tillage. The final product was assessed only corn. The technical coefficients, the workload, performance, identification of the tractor, implements and equipment, their specifications and their consumption of fuel, lubricants and greases, as well as quantification of manpower used were derived from primary data and secondary. The methodology consisted of determining the "Efficiency Cultural Partial" and "Energy Efficiency Partial". Regarding the energy balance in part, cultural and energy efficiency partial there were no major differences between the systems studied. We conclude that the conditions of the experiment the conduction system assessed in terms of energy both systems have the same performance.

O conhecimento da produção e o dispêndio de energia pela agricultura é fundamental devido à importância estratégica que ocupa como produtora de insumos energéticos para outros setores econômicos, como é o caso do biodiesel produzido a partir de culturas oleaginosas; desta forma, o presente estudo teve como objetivo determinar os custos energéticos parciais da implantação e condução do agroecossistema milho em consórcio com pinhão-manso, sob os sistemas de condução sequeiros e irrigados, em experimento conduzido de acordo com o sistema produtivo da agricultura familiar da região oeste do Paraná. Tal estudo se justifica devido à escassez de dados energéticos da cultura do pinhão-manso em condições brasileiras, bem como em sistema consorciado sob condições tecnológicas da agricultura familiar do oeste paranaense e, sobretudo, das questões ambientais envolvidas neste estudo como o uso racional de fontes energéticas não renováveis. O experimento foi conduzido de acordo com as técnicas empregadas por agricultores familiares da região oeste paranaense, no período de fevereiro de 2008 a maio de 2008 para a cultura do milho e de fevereiro de 2008 a novembro de 2009, para a cultura do pinhão-manso, no Núcleo Experimental de Engenharia Agrícola (NEEA), pertencente à Universidade Estadual do Oeste do Paraná (UNIOESTE), campus de Cascavel/PR, em área de plantio direto. O produto final avaliado foi apenas o milho. Os coeficientes técnicos, a jornada de trabalho, o rendimento, a identificação do trator, implementos e equipamentos, suas especificações e respectivos consumos de combustível, lubrificantes e graxas, além da quantificação da mão-de-obra utilizada foram determinados a partir de dados primários e secundários. A metodologia adotada constituiu-se de determinação da “Eficiência Cultural Parcial” e “Eficiência Energética Parcial”. Com relação ao balanço energético parcial, eficiência cultural e energética parciais não houve grandes diferenças entre os sistemas estudados. Conclui-se que para as condições do experimento e para os sistemas de condução avaliados, do ponto de vista energético ambos os sistemas têm o mesmo desempenho.
Energy costs agroecosystem physic-nut-corn: comparing the conduction rainfed system with irrigated
Keywords: Biofuel; Intercropping; Family farming; Biodiesel; Consórcio de culturas; Agricultura familiar